Health technology assessment and reimbursement of pharmaceuticals in Italy - F. V. Gorkavenko; V. V. Omelyanovskiy; T. P. Bezdenezhnykh; G. R. Khachatryan (Фармакоэкономика, 2019)
The Italian healthcare system is historically structured by the difference in economic development between the northern and southern parts of this country. The Italian Medicines Agency (AIFA) is the national health technology assessment (HTA) authority in charge of the reimbursement and formulary-listing. Some regions have established their own HTA institutions to define the reimbursement policy for a specific region or organization. Because of that, the entire HTA system in Italy can be characterized by low inter-regional coherence and insufficient coordination. As a result, the access to medical services is not unified at the regional level; in addition, it is difficult to collect and analyze the data required for providing value-based healthcare. Although the cost-effectiveness of specific health technologies is taken into consideration for decision-making, in practice, the main focus rests on the budget impact and cost control. Along with that, the AIFA holds the leading positions in Europe in using such innovative approaches as the patient access schemes, early HTA and horizon scanning.